The Effect of Financial Constraints and Political Connections on Tax Aggressiveness with ESG Disclosure as a Moderating Variable - Hajriati, Tuty; Rahman, Aulia Fuad; Rusydi , Mohamad Khoiru (Atestasi : Jurnal Ilmiah Akuntansi, 2024)
This study investigated the effect of financial constraints and political connections on tax aggressiveness. Additionally, ESG disclosure was used as a moderating variable to examine the impact of financial constraints and political connections on tax aggressiveness. Quantitative research uses secondary data. Data was collected from company reports, annual reports, and sustainability reports. The data was analyzed using hypothesis tests. The results of this study demonstrated that financial constraints and political connections positively influenced tax aggressiveness. Furthermore, this study revealed that ESG disclosure could weaken the positive influence of financial constraints on tax aggressiveness. In addition, ESG disclosure did not moderate the influence of political connections on tax aggressiveness. The tax authority can improve PMK No. 22/PMK.03/2020, about procedures for implementing transfer price agreements in unique company relationships by considering ESG disclosure to prevent an increase in tax aggressiveness. This study adds ESG disclosure to classify the inconsistency of previous research (Adela et al., 2023; Solikin & Slamet, 2022; Octaviani & Sofie, 2018), which are thought to have a combined influence on the financial constraints and political connections on tax aggressiveness.